Advanced information systems engineering workshops : CAiSE 2018 International Workshops, Tallinn, Estonia, June 11-15, 2018, Proceedings /: CAiSE 2018 International Workshops, Tallinn, Estonia, June 11-15, 2018, Proceedings. (2018) - Unknown
No abstract available